Oral Health-Related Quality of Life (OHRQoL) Analysis in Partially Edentulous Patients with and without Denture Therapy - Berniyanti T; Palupi R; Alkadasi BA; Sari KP; Putri R I; Salma N; Prasita S; Regita A S (Dove Medical Press, 2023)
Titiek Berniyanti,1 Retno Palupi,1 Baleegh Abdulraoof Alkadasi,2 Kartika Putri Sari,3 Indriasari Putri R,4 Nadhifa Salma,4 Shafa Prasita,4 Stephanie Regita A4 1Department of Dental Public Health, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Indonesia; 2Department of Periodontology and Oral Medicine, Faculty of Dentistry, Ibb University, Ibb, Yemen; 3Graduate Student of Dental Health Science, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Indonesia; 4Graduate Student, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, IndonesiaCorrespondence: Titiek Berniyanti, Perum ITS Block J8 Keputih Sukolilo, Surabaya, 60111, East Java, Indonesia, Tel +62 81330788776, Fax +62 31 5030255, Email titiek-b@fkg.unair.ac.idPurpose: One of the Indonesians oral health problems today is teeth loss. Several treatments can be done to overcome the problems, especially to restore missing teeth function, which are mastication, speech function, and improve aesthetic. The aim of this study was to analyze the correlation between oral health-related quality of life (OHRQoL) domains physical health, psychological health, social relationships, environment, and the domain of Oral Impact on Daily Performance (OIDP) in partially edentulous patients with implants, conventional dentures, and non-users (without implant and conventional denture).Patients and Methods: This is a cross-sectional analytic observational study. Samples were partially edentulous patients aged 15- 70 in Surabaya were taken using a simple random sampling technique within inclusion criteria. Reliability and validity analysis was carried out with Eta correlation test and then comparative analysis was performed with Kruskal Wallis and Post Hoc test with Mann Whitney U-Test. All procedures were carried out in accordance with the relevant guidelines and regulations by Ethics Committee, Faculty of Dental Medicine, Unair, Surabaya, Indonesia (No: 441/HRECC.FODM/VII/2022).Results: The results showed that there was a significant correlation between partially edentulous patients with and without dentures with the domains of physical health, psychological health, social, environment, and the domain of OIDP.Conclusion: The study showed a statistically significant correlation between OHRQoL domain of physical health, psychological health, social and environment, and the domain of OIDP in partially edentulous patients with implants, conventional dentures, and non-users (without implants and conventional dentures). Edentulism is really felt by the people and has a negative effect meaningful to the physical, economic, and psychological. For this reason, in determining the use of implants, conventional dentures, and non-users (without implants and conventional dentures) it is important to consider domains of OHRQoL consisting of physical health, psychological health, social relationships, environment, and the domain of OIDP.Keywords: implant, physical health, psychological, social, good health and well being